Harold Garfinkel: Studies of Work in the Sciences - Garfinkel, Harold (Directions in Ethnomethodology and Conversation Analysis, 2022)
This volume includes an unpublished manuscript and selected portions of five seminars by Harold Garfinkel - the founder of ethnomethodology - on the topic of practices in the natural sciences and mathematics. The volume provides a coherent and sustained account of his program for the study of ordinary and specialized social actions. Presenting broader theoretical and methodological initiatives, as well as discussions and summaries of exemplary studies of social phenomena within and beyond the sciences, this work dates to the period in the 1980s during which the field of Science and Technology Studies was taking shape, with ethnomethodological studies of scientific practice forming a major part of its development at the time. Aside from their historical importance, the manuscript and seminars present a distinctive perspective on the natural and social sciences that remains highly original and pertinent to research on science, social science, and everyday life today. Offering critical insights and proposals relating to developments in Ethnomethodology and Conversation Analysis, this volume will appeal to scholars of Sociology and Science and Technology Studies with interests in the work of Garfinkel.